UNSUR-UNSUR KEBUDAYAAN DALAM TEKS NGGAHI DANA PADA MASYARAKAT DOMPU: SUATU PENDEKATAN ARKETIPEL-PRAGMATIK - Wawan Irawan; Johan Mahyudi; Muhammad Sukri (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This research aims to analyze, track and formulate the social perspective in Dompu societies that are implied and expressed in text of Nggahi Dana. Arcetype-pragmatic approach was used as the research design emphasizing on content and thematic analysis.  Seven informants were assigned as the key informants.  In addition, observations, interviews and documents analysis were applied to support the data. Three video-tapes obtained from the observation and interviews were transcribed verbatim prior to analysis. The study reveals that identity construction of societies in Dompu was made by culture politics through oligarchy hierarchy since several years ago, that is to obey to the leader and abroad guests, and the text of Nggahi Dana is utilized as the device to doctrine low level societies (slave) by the rulers.